AN ACTIVE POWER FILTER AT OPERATION ON THE UNBALANCED AND NONLINEAR LOADS WITH CONTROL BY OPTIMIZATION ALGORITHM - E. V. Yagup (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose is to develop a method for controlling a power active filter based on search optimization using software of Mathlab package and applying this method for balancing and compensating for all components of reactive power in a three-phase system feeding unbalanced linear and nonlinear loads simultaneously. Methodology consists in the development of a visual model of the power supply system that supplies unbalanced and non-linear loads, to the connection points of which a power active filter on IGBT transistors is connected according to a parallel type scheme. We propose an algorithm for calculating the chosen optimization criterion using a visual model, linking the visual model with an optimizing program, and performing a search engine optimization process using an embedded program that implements the deformable polyhedron algorithm. Results lead to an optimal mode, which is characterized by the amplitudes of the control signals of the power active filter control system determined by the search, as well as the initial value of the voltage on the filter energy exchange capacitor. Originality lies in the fact that the proposed method of controlling the operation of the power filter makes it possible to dispense with the construction of a relatively complex filter control system based on Clark's mathematical transformations. Practical value lies in the fact that finding a quasi-steady-state optimal mode of the power supply system with a power active filter is performed automatically in the process of search optimization with a simplified control system. The above principles can be implemented in the microprocessor control system for power active filters.